Implementation of Education-Based Community Service to Increase Environmental Awareness among Young People - Septi Viantri Kurdaningsih; Esa Zahirah (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
The present study aims to investigate the impact of community service based on environmental education on increasing environmental awareness among Indonesian youth. The present study employed a descriptive quantitative approach, utilising a pre-experimental design of a single group, pretest-posttest type. These coding techniques were employed to identify narrative patterns, group dynamics and the supporting and inhibiting factors that emerged during the learning process. The descriptive analysis demonstrated a significant increase in all indicators of environmental awareness following the implementation of the community service-based education programme, including participants' knowledge, attitudes, behaviours, and self-efficacy. Furthermore, a significant increase in attitudes was observed, from an initial score of 68.2 to a post-intervention score of 86.7. These results underscore the significance of programme design that integrates critical learning theory, transformative approaches, and community participation in fostering a generation that is aware of, concerned about, and actively engaged in environmental sustainability. It is hoped that this initiative will set a precedent for sustainable community service and make a meaningful contribution to the development of a future-oriented environmental agenda.